Considerations for Establishing a Behavioral Policy-Making and Nudge Institution within the Country's Executive Structure - Seyed Kamal Vaezi; Maryam Darbandi (مدیریت دولتی)
ObjectivePublic interest in behavioral interventions within the field of public policy has expanded significantly in recent years, largely due to a growing understanding of human behavior and decision-making. In Iran, there is increasing recognition of the need for both theoretical and practical considerations in the adoption of behavioral policy-making. This article examines the feasibility and strategic approach for establishing behavioral insight teams within Iran’s executive structure and decision-making processes. By drawing on experiences from both advanced and developing countries that have integrated behavioral insight teams into their governance frameworks, the study focuses on the potential establishment of a behavioral insight policy institution within the policy-making apparatus of Iran. Additionally, it evaluates the key organizational and structural considerations necessary for successfully embedding such an institution within the executive framework of the country.MethodsThis study adopts a qualitative research methodology, specifically employing thematic analysis to obtain an in-depth understanding of expert perspectives on behavioral policy. The target population includes university faculty members, executives, specialists, and practitioners active in the field of behavioral policy. Using snowball sampling, a total of 14 participants were initially interviewed, with two additional interviews conducted to ensure theoretical saturation. Experts were asked to respond to 10 structured sub-questions, eliciting their views on the feasibility of establishing a behavioral insight policy body and the organizational considerations for embedding it within Iran’s executive structure. Through this rigorous interview process, a wealth of qualitative data was gathered to assess both the potential and the challenges associated with forming a dedicated behavioral insight institution.ResultsThe literature review summarizes the experiences of countries with behavioral insight teams, presenting them in three areas: operational goals and tasks, institutional and organizational structure, and legal frameworks. Based on interviews with Iranian experts, the study identified 294 fundamental themes, which were organized into 8 main categories, including organizational structure, legal considerations, societal behavior, behavioral tendencies of government officials, bureaucratic ethics, and the degree of acceptance of theoretical concepts related to organizational behavior. These themes highlight both enabling factors and potential barriers to establishing a behavioral insight team within Iran’s unique governance context.ConclusionThe study suggests that successful implementation of behavioral management systems in Iran requires careful attention to institutional, philosophical, and behavioral considerations. Institutionally, it is recommended that behavioral insight teams operate outside the primary administrative governance body to maintain objectivity. After harmonization, evaluation, awareness-building, and non-mandatory recommendations, these teams can be gradually integrated within the governance structure. From a behavioral perspective, policymakers must deepen their understanding of both Iranian societal and government officials' behaviors to tailor interventions effectively. Given Iran's cultural orientation toward ideological rather than technocratic rationality, behavioral interventions must be adapted to an Iranian narrative. An Iran-specific approach to behavioral policy, emphasizing culturally resonant nudges and superstructural adjustments, is necessary to ensure acceptance and efficacy.